1995
DOI: 10.1002/jid.3380070111
|View full text |Cite
|
Sign up to set email alerts
|

The social and economic impact of HIV/AIDS on farming systems and livelihoods in rural Africa: Some experience and lessons from Uganda, Tanzania and Zambia

Abstract: This article describes: (1) some of the effects of HIV/AIDS on rural communities in cast and southern Africa (2) the indications for the development of such impacts in Uganda, Tanzania and Zambia over the medium term, noting similarities and differences between the three countries; (3) explores the policy implications of these findings; (4) presents a generalised response strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…45 Barnett et al (1995) in Uganda evidence present evidence of households shifting farming activity away from high value cash crops toward crops for own consumption. For rural Kenya, Yamano and Jayne (2004), using household fixed effects, find no change in area devoted to food crops after an adult death but a large reduction in area allocated to cash crops such as coffee and tea if the death is of a male head of household.…”
Section: Methodological Concernsmentioning
confidence: 99%
“…45 Barnett et al (1995) in Uganda evidence present evidence of households shifting farming activity away from high value cash crops toward crops for own consumption. For rural Kenya, Yamano and Jayne (2004), using household fixed effects, find no change in area devoted to food crops after an adult death but a large reduction in area allocated to cash crops such as coffee and tea if the death is of a male head of household.…”
Section: Methodological Concernsmentioning
confidence: 99%
“…The Kenya government has employed public education to prevent new HIV infections and provision of anti-retroviral (ARV) drugs to the infected persons to increase their lifespan and improve the quality of lives. The government has also increased access to education through provision of free basic education, increase in academic institutions among others since education in itself is an important tool in combating HIV and AIDS [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Uganda, Tanzania and Zambia have shown that HIV/AIDS follows a different pattern in each village and district [12]. Geographic and ethnic factors, religion, gender, age, marriage, customs and agro-ecological conditions play a role in the pattern and impact of HIV/AIDS and in people's perception of the disease.…”
Section: Introductionmentioning
confidence: 99%